Prototype Biodigester Biogas dengan Sistem Monitoring Berbasis Internet of Things (IoT) - Muhammad Zhaky; Dinda Asyifa; Eko Supriadi; Oktrison Oktrison (Jurnal Universal Technic, 2025)
Biogas is a renewable energy source with significant potential to reduce dependence on fossil fuels. However, conventional biodigester systems still face several challenges in monitoring methane gas production. Therefore, this research aims to design and develop a biogas digester prototype equipped with a stirrer and an Internet of Things (IoT)-based sensor to detect methane (CH4) gas levels. The research methodology involves designing a biodigester with an automatic stirrer and an MQ-2 sensor that can detect methane gas levels in real time. The data obtained is transmitted via ESP32 and displayed on the Blynk application. The research results show that the designed system can increase methane gas production and allow remote monitoring. The conclusion of this study is that the integration of IoT technology in the biodigester system can improve production efficiency and safety in biogas utilization.